Ruminal ammonia load does not affect histidine utilization in growing steers - K.C. Candler; M.S. Awawdeh; D.P. Gnad; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2003)
Fermentation of dietary protein in the rumen leads to ammonia absorption, which could impair amino acid utilization in cattle. Our study was conducted to determine the effects of rumen ammonia load on histidine utilization. Six ruminally cannulated Holstein steers (318 lb) housed in metabolism crates were used in a 6 x 6 Latin square design. Treatments were arranged as a 3 x 2 factorial and included: 0, 1.5, or 3 grams/day L-histidine infused abomasally; and 0 or 80 grams/day urea infused ruminally to supply a metabolic ammonia load. As expected, urea infusions increased rumen ammonia and plasma urea concentrations. No change in nitrogen retention, a measure of lean tissue growth, occurred in response to urea. Retained nitrogen increased with histidine supply, and the maximal response occurred with 1.5 grams/day of histidine, suggesting that this amount was near the supplemental requirement. Our research revealed that increases in ammonia load did not demonstrate a metabolic cost in terms of whole body protein deposition, regardless of whether histidine was limiting. Thus, although an excess protein supply may not be economically efficient or environmentally friendly, it does not appear to directly penalize animal performance.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Ruminal ammonia; Histidine; Steers